Stimulation of angiogenesis and survival of endothelial cells by human monoclonal Tie2 receptor antibody. (May 2015) - Hwang, Byungtae; Lee, Sang-Hyun; Kim, Jang-Seong; Moon, Ji Hyun; Jeung, In Cheul; Lee, Na Geum; Park, Jongjin; Hong, Hyo Jeong; Cho, Young-Lai; Jung, Haiyoung; Park, Young-Jun; Lee, Seon-Jin; et al.
Abstract: Angiopoietin-1 (Ang1) and its endothelium-specific receptor, tyrosine kinase with Ig and epidermal growth factor homology domain 2 (Tie2), play critical roles in vascular development. Although the Ang1/Tie2 system has been considered a promising target for therapeutic neovascularization, several imitations of large-scale production have hampered the development of recombinant Ang1 for therapeutics. In this study, we produced a fully human agonistic antibody against Tie2, designated 1–4h, and tested the applicability of 1–4h as an alternative to native Ang1 in therapeutic angiogenesis. 1–4h significantly enhanced the phosphorylation of Tie2 in a dose- and time-dependent manner in human Tie2-expressing HEK293 cells and human umbilical vein endothelial cells. Moreover, 1–4h induced the activation of Tie2-mediated intracellular signaling such as AKT, eNOS, MAPK, and Focal Adhesion Kinase p125 FAK . In addition, 1–4h increased the chemotactic motility and capillary-like tube formation of endothelial cells in vitro and enhanced the survival of serum-deprived endothelial cells. Taken together, our data clearly suggest that a human Tie2 agonistic antibody is a potentially useful therapeutic approach for the treatment of several ischemic diseases including delayed-wound healing and ischemic heart and limb diseases.